Lagos: Ownership and Identities Audio Interview 1 - Lawanson, Taibat; Eleshin, Abisoye (Lagos Ownership and Identities (Intellectual Debates and One Month Photography Exhibition), 2023)
Audio recording of interview
Keywords: History; Migration; African Studies; Lagos; Knowledge